The Netherlands Chlamydia cohort study (NECCST) protocol to assess the risk of late complications following Chlamydia trachomatis infection in women - Hoenderboom, B. M. (BMC Infect Dis, 2017)
BACKGROUND: Chlamydia trachomatis (CT), the most common bacterial sexually transmitted infection (STI) among young women, can result in serious sequelae. Although the course of infection is often asymptomatic, CT may cause pelvic inflammatory disease (PID), leading to severe complications, such as prolonged time to pregnancy, ectopic pregnancy, and tubal factor subfertility. The risk of and risk factors for complications following CT-infection have not been assessed in a long-term prospective cohort study, the preferred design to define infections and complications adequately. METHODS: In the Netherlands Chlamydia Cohort Study (NECCST), a cohort of women of reproductive age with and without a history of CT-infection is followed over a minimum of ten years to investigate (CT-related) reproductive tract complications. This study is a follow-up of the Chlamydia Screening Implementation (CSI) study, executed between 2008 and 2011 in the Netherlands. For NECCST, female CSI participants who consented to be approached for follow-up studies (n = 14,685) are invited, and prospectively followed until 2022. Four data collection moments are foreseen every two consecutive years. Questionnaire data and blood samples for CT-Immunoglobulin G (IgG) measurement are obtained as well as host DNA to determine specific genetic biomarkers related to susceptibility and severity of infection. CT-history will be based on CSI test outcomes, self-reported infections and CT-IgG presence. Information on (time to) pregnancies and the potential long-term complications (i.e. PID, ectopic pregnancy and (tubal factor) subfertility), will be acquired by questionnaires. Reported subfertility will be verified in medical registers. Occurrence of these late complications and prolonged time to pregnancy, as a proxy for reduced fertility due to a previous CT-infection, or other risk factors, will be investigated using longitudinal statistical procedures. DISCUSSION: In the proposed study, the occurrence of late complications following CT-infection and its risk factors will be assessed. Ultimately, provided reliable risk factors and/or markers can be identified for such late complications. This will contribute to the development of a prognostic tool to estimate the risk of CT-related complications at an early time point, enabling targeted prevention and care towards women at risk for late complications. TRIAL REGISTRATION: Dutch Trial Register NTR-5597. Retrospectively registered 14 February 2016.